(untitled) ("Conference on Universal Science Research 2023", 2023)
Formation of higher knowledge, skills and qualifications in primary grades activities aimed at increasing the effectiveness of educational activities for It is also important to study the issues of students’ motivations becomes important. This article provides information about the psychological factors of the formation of learning motivation in elementary school students.